Hubungan tingkat pengetahuan kepala keluarga tentang kepatuhan menerapkan protokol kesehatan saat pandemi Covid-19 - Lathifah, Ummi; Syarifah, Nur Yeti; Hidayat, Nur (STIKES Wira Husada Yogyakarta, 2022)
Background: The Covid-19 pandemic has hit various countries including Indonesia. The number of Covid-19 cases in Indonesia is increasing every day. Ngleri Lor Hamlet, Ngleri Village, Playen District, Gunungidul Regency is one of the hamlets that has Covid-19 cases. The number of positive confirmed cases of Covid-19 in Ngleri Lor Hamlet currently (Mari 2021) is 2 cases. For this reason, efforts are needed to break the chain of transmission of Covid-19 that involves all elements of society. This knowledge about Covid-19 is very important for the community so that people are able to make decisions in appropriate behavior in order to break the chain of transmission of Covid-19.Objective: To determine the relationship between the level of knowledge of the head of the family regarding compliance with implementing the Covid-19 protocol in the Ngleri Lor Hamlet.Methods: This research is an analytic observational study with a cross sectional research design. Samples were taken using the accidental sampling method. The measuring instrument used is a questionnaire. Data analysis using Chi-Square correlation test.Results: The results of the study using the Chi-Square test obtained a p value of 0.000 which means there is a significant relationship between Knowledge Level and Compliance with implementing the Covid-19 protocol in Ngleri Lor Hamlet.Conclusion: The knowledge and compliance of the majority of the people of Dusun Ngleri Lor Hamlet were good. This condition is expected to support efforts to handle the Covid-19 case in Ngleri Lor Hamlet, Ngleri Village, Playen District, Gunungkidul Regency. However, monitoring from the government and community members is still needed to maintain a conducive situation in efforts to break the chain of transmission of Covid-19.